Development of molecularly imprinted polymer membranes with specificity to triazine herbicides, prepared by the "surface photografting" technique - Sergeyeva, T.A.; Matuschewski, H.; Piletsky, S.A.; Schedler, U.; Ulbricht, M. (Біополімери і клітина, 2004)
«Surface photografting» of polypropylene (PPy) microporous membranes by molecularly imprinted polymers selective to triazine herbicides has been carried out by the UV irradiation-initiated co-polymerization of the functional monomer (2-acrylamido-2-methyl-1-propane sulphonic acid) and a cross-linker (N,N?-methylene-bis-acrylamide) in the presence of the template (terbumeton) onto photoinitiator (benzophenone)-coated samples. The grafting reaction occurs in a thin liquid layer on the membrane substrate, which is pre-soaked in a dimethyl formamide solution containing template, functional monomer and cross-linker. After irradiation with a 500 W mercury lamp for 10 min at room temperature, the membranes covered with the layer of imprinted polymer were obtained. The recognition sites complementary to terbumeton were formed in the membranes after extraction of the template molecules with methanol. Alternatively, reference polymeric membranes were prepared with the same monomer composition, but without the template. The membranes' recognition properties were estimated by their capability to herbicide adsorption from its aqueous solution. The membranes modified by the mixture of monomers containing terbumeton showed significantly higher adsorption capability to this herbicide than to analogous compounds (terbuthylazine, atrazine, desmetryn, metribuzine). The effect of the polymer composition on the binding properties of the membranes has been investigated. High affinity of these membranes to triazine herbicides together with their inexpensive preparation, provide a good basis for applications of molecularly imprinted polymer membranes in separation and solid-phase extraction. Синтезовано новий тип матричних полімерних мембран шляхом поверхневої модифікації мікрофільтраційних поліпропі ленових мембран, яка полягала в нанесенні на поверхню тонкого шару матричного полімеру, селективного до триазинового гербіциду тербуметону. Матричну полімеризацію здійснювали в диметилформаміді, використовуючи гербіцид тербуметон як матрицю, 2-акриламідо-2-метил-1-пропан-сульфонову І метакрилову І акрилову кислоту як функціональний мономер і N ,N' -метилен-бісакриламід як зшивальний агент на поверхні мікрофільтраційної мембрани, покритої тонким шаром фотоініціитора бензофенону. Екстракція матричних молекул спричинювала формування в структурі мембрани сайтів, які за формою та проепюровим розташуванням функціональних груп були комплементарними тербуметону. Контрольні мембрани модифікували з використанням подібної суміші мономерів, що не містила тербуметону. Здатність мембран до селективної адсорбції тербуметону досліджено в залежності від типу та концентрації функціонального мономера, а також від концентрації зшивального агента в мономерній суміші. Показано, що тербуметон-імпринтовані матричні полімерні мембрани характеризуються високою селективністю стосовно тербуметону та здатністю до незначної адсорбції його структурних аналогів — тертбутилазину, атразину, десметрину і метрибузину. Такі властивості синтезованих мембран забезпечують їхнє ефективне використання у твердофазовій екстракції. Синтезирован новый тип матричных полимерных мембран методом поверхностной модификации микрофильтрационных полипропиленовых мембран, заключающемся в нанесении на поверхность тонкого слоя матричного полимера, селективного к триазиновому гербициду тербуметону. Матричную полимеризацию проводили в диметилформамиде с использованием триазинового гербицида тербуметона в качестве матрицы, 2-акриламидо-2-метил-1-пропан-сульфоновойї метакриловой акриловой кислоты как функционального мономера и N,N'-метилен-би сак рилам ида как сшивающего агенпш на поверхности микрофильтрационной мембраны, покрытой тонким слоем фотоинииштюра бензофенона. Экстракция матричных молекул приводила к формированию в структуре мембраны сайтов, комплементарных тербуметону по форме и пространственному расположению функциональных групп. Контроль ные мембраны синтезоровали с использованием той же мономерной смеси в отсутствие тербуметона. Способность мем бран к селективной адсорбции тербуметона исследовали в зависимости от типа и концентрации функционального мономера, а также концентрации сшивающего агента, в мономерной смеси. Показано, что тербуметон-импринтированные матричные полимерные мембраны характеризуются высокой селективностью к тербуметону и демонстрируют незначительную адсорбцию его структурних аналогов — тертбутилазина, атразина, десметрина и метрибузина. Такие свойства синтезованных мембран обеспечивают возможность их эффективного использования в твердофазной экстракции.